Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18502/ijhoscr.v12i4.105
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Bleeding Disorders in Iraq and Consanguineous Marriage

Abstract: Background: Consanguineous marriage is defined as inbreeding between second cousins or closer. In such families there will be a potential increase in the autosomal recessive traits with its lethal effect, with an increased risk of morbidity and mortality in the new generation.  Inherited bleeding disorders (InBDs) are rare complicated diseases, difficult and expensive to treat, the defect usually due to quantitative or qualitative deficiency of clotting factors, platelets or fibrinolysis. This study attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Parental consanguinity among 31 CF patients was 87.1%. This is higher than the average consanguinity rates among Iraqi general populations (40–49%) [ 10 ] but similar to the rates reported for other hereditary conditions in Iraq [ 11 ]. This finding also helps to explain the increasing occurrence of rare conditions such as CF and familial aggregation of patients which is seen in 5 (16.13%) patients, similar to that reported in other regional countries [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 76%
“…Parental consanguinity among 31 CF patients was 87.1%. This is higher than the average consanguinity rates among Iraqi general populations (40–49%) [ 10 ] but similar to the rates reported for other hereditary conditions in Iraq [ 11 ]. This finding also helps to explain the increasing occurrence of rare conditions such as CF and familial aggregation of patients which is seen in 5 (16.13%) patients, similar to that reported in other regional countries [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 76%
“…In lieu of epidemiological surveys, several intuitional-based studies assessed prevalence of inherited bleeding disorders on smaller scale in Saudi population, however, the focus and scope of these studies have been vWD, haemophilia A, haemophilia B, and platelet disorders. [ 23 25 ] El-Bostany et al [ 20 ] evaluated prevalence of vWD, haemophilia A, haemophilia B, and platelet disorders in 43 children, while Ahmed et al [ 26 ] reported 15 cases of haemophilia, 1 case of VII deficiency, 1 case of X deficiency and 12 cased of Glanzmann thrombasthenia. Al-Sharif et al [ 27 ] reported 17 cases with factor XIII deficiency in Riyadh region.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence is important, as Arab populations have a higher prevalence of bleeding disorders than Western population, primarily due to the increased consanguinity ratio in Arab communities. [ 23 ] The current study provides prevalence information with respect to geographical distribution and genetic disparity of various bleeding disorders signifying the requirement for surveillance-system to identify and register individuals with bleeding symptom. Moreover, gender disparity clearly highlights the need for genetic mapping to identify the families and individuals at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 10 FX deficiency is more prevalent in regions where consanguineous marriage remains common, such as in the Middle East. 9 11 12 Deficient patients experience variable bleeding symptoms, ranging from easy bruising, gum bleeding, nose bleeds and hematuria in mild cases to hemarthrosis, hematomas, intramuscular bleeds, gastrointestinal tract bleeds, and intracranial hemorrhage in more severe cases. All FX deficient patients are at greater risk of prolonged postoperative bleeding.…”
Section: Introductionmentioning
confidence: 99%